Air Doa dalam Tradisi Pembacaan Hizib Nahdhatul Wathan: Studi Living Qur’an di Desa Sembalun Bumbung, Lombok Timur - Wulandari, Suci; Rahman, Abd. (Canonia Religia, 2023)
This article discusses the phenomenon of "air doa" (prayer water) in the tradition of reading the hizib Nahdlatul Wathan (NW) in Sembalun Bumbung. Several research questions are posed to answer the forms and typologies of the reception of the Quran, as well as the role of local leaders in the transmission and transformation of knowledge regarding this tradition to the community. In this research, the author employs a qualitative phenomenological approach and the theory of the reception of the living Quran. Data collection is carried out through interviews, observations, and documentary studies. The results of the analysis indicate that the functional (practical) reception of the people of Sembalun Bumbung is evident in their beliefs about the efficacy of prayer water in the tradition of reading the hizib NW, including its use for healing, health, agricultural fertility, and intellectual blessings. In this context, the local leader is TGKH. Zainuddin Abdul Madjid, who plays the role of the carrier and teacher of the hizib NW in Sembalun Bumbung. The process of transmitting and transforming knowledge related to prayer water in the tradition of reading the hizib NW is closely tied to the local leader's knowledge of the history of healing during the time of the Prophet, the Companions, and early scholars, as well as the existing Sasak belian tradition in Sembalun Bumbung. The phenomenon of prayer water in the tradition of reading the hizib NW demonstrates that the Quran is alive and integrated into the everyday life of the people of Sembalun Bumbung. [Artikel ini membahas tentang fenomena air doa dalam tradisi pembacaan hizib Nahdlatul Wathan (NW)  di Sembalun Bumbung. Sejumlah pertanyaan penelitian yang diajukan untuk menjawab tentang bentuk dan tipologi resepsi al-Qur’an, serta peran local leader dalam proses transmisi dan  transformasi pengetahuan atas tradisi tersebut kepada masyarakat. Dalam penelitian ini, penulis menggunakan pendekatan kualitatif fenomenologi dan teori resepsi-living Qur’an. Pengumpulan data dilakukan melalui wawancara, observasi, dan studi dokumentasi. Hasil analisis menunjukkan bahwa resepsi fungsional (praktis) masyarakat Sembalun Bumbung tampak dalam kepercayaan mereka mengenai khasiat air doa dalam tradisi pembacaan hizib NW, di antaranya untuk kesembuhan penyakit, kesehatan, kesuburan pertanian, dan barokah kecerdasan. Dalam konteks ini, local leader adalah TGKH. Zainuddin Abdul Madjid, berperan sebagai pembawa dan pengajar hizib NW di Sembalun Bumbung. Adapun proses transmisi dan transformasi pengetahuan terkait air doa dalam tradisi pembacaan hizib NW tidak terlepas dari pengetahuan local leader mengenai sejarah pengobatan di masa Rasulullah, Sahabat, dan para ulama terdahulu, serta tradisi belian Sasak yang sudah ada di Sembalun Bumbung. Fenomena air doa dalam tradisi pembacaan hizib NW ini menunjukkan bahwa al-Qur’an hidup dan menyatu dalam kehidupan sehari-hari masyarakat Sembalun Bumbung.]